DEVELOPMENT OF HIGH STRENGTH FIBRE REINFORCED CONCRETE WITH ENHANCED DUCTILITY - ULLAH KHAN, SADAQAT (2015)
The endeavour of this research is to develop High strength fibre reinforced concrete (HSFRC) of higher ductility and low cost. Polyvinyl alcohol (PYA) Fibres and metakaolin as cement replacing material were used. The study was conducted in three phases. In phase L the Malaysian kaolin was calcined and the optimum condition of calcination was determined in order to achieve highly reactive metakaolin. Also. the characteristics and cost of producing metakaolin have been determined to justify its potential application. In Phase II. total fifty (50) mixes of concrete were prepared. The qualified mixes based on the criteria of cube compressive strength (90 MPa at 28 days) and deflection-hardening response was then identified. In phase Ill, the qualified mixes were investigated under direct tension to determine their response. Also. all the mechanical properties of l-ISFRC were utilised in developing predictive model tor the mechanical properties of IISFRC by regression analysis and by Artificial Neural Network (ANN).